The Representations of Educational Change - María del Mar Rodríguez Romero (Universidad Autónoma de Baja California, 2000)
This article explores the conceptual limits that the dominant metaphors of educational change impose upon us, and their intimate connection to representations of educational change. It analyzes two prominent educational change representations. One representation captures educational change in movement, and employs notions such as cycles, waves, tendencies and ruptures. The other expresses the relationship between stability and change, and illustrates its paradoxical nature by declaring its commitment to transformation, but without breaking through the boundaries of the status quo. The purpose is to reconsider the emancipating intentions of the critical proposals, relating modernist images of progress and change with post-structuralist and postmodern categories.